The Decline of Javanese Krama Culture in The Modernization Era - Nisa', Khoirun (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study aims to describe the decline in the culture of the use of Javanese Krama language in the era of mosdernization.This research uses qualitative methods with the type of research study of documentary research or research through sources of books, journals, articles, and other documentation materials sourced from libraries. data analysis researchers use content analysis or methodologies that utilize. using a set of procedures to draw a conclusion sourced from books or documents and done objectively. The results of this study indicate a decline in the culture of using Javanese Krama in the era of modernization indicated by the transition of Javanese language users or mixing with other languages and adjusting the language used. There are 5 factors affecting the decline in the culture of Javanese Krama language use, namely bilingualism, migration, economic development, the existence of a language status that is considered high or social strata and colonization.